2010
DOI: 10.2203/dose-response.09-019.fornalski
|View full text |Cite
|
Sign up to set email alerts
|

The Healthy Worker Effect and Nuclear Industry Workers

Abstract: The linear no-threshold (LNT) dose-effect relationship has been consistently used by most radiation epidemiologists to estimate cancer mortality risk. The large scattering of data by International Agency for Research on Cancer, IARC (Vrijheid et al. 2007; Therry-Chef et al. 2007; Cardis et al. 2007), interpreted in accordance with LNT, has been previously demonstrated (Fornalski and Dobrzyński 2009). Using conventional and Bayesian methods the present paper demonstrates that the standard mortality ratios (SMRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…In line with this, Flanders showed that time-since-hire was associated with decline in health and could therefore cause an artificial adverse effect of cumulative exposure [28] in the opposite direction as HWE. Consistently, Howe argues that the maximal lowered mortality is observed during the first five years of employment [10]. These results seem in line with ours indicating an effect modification by age.…”
Section: Discussionsupporting
confidence: 91%
“…In line with this, Flanders showed that time-since-hire was associated with decline in health and could therefore cause an artificial adverse effect of cumulative exposure [28] in the opposite direction as HWE. Consistently, Howe argues that the maximal lowered mortality is observed during the first five years of employment [10]. These results seem in line with ours indicating an effect modification by age.…”
Section: Discussionsupporting
confidence: 91%
“…Most studies find an average underestimation of about 25% of the association of a noxious stimulus on mortality as a result of HWE. [ 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 ] This underestimation of risk implies that being exposed to the noxious stimulus was protective. [ 17 18 19 20 21 ] HWE may not be complete and may only partially mask the excess mortality[ 19 ] and in rare cases may not be protective.…”
Section: U Nderstanding H Ealthymentioning
confidence: 99%
“…The so-called healthy worker effect is a commonly found phenomenon in occupational epidemiology [20], which is reflected in the standardized rate ratio as being less than one when compared to the external control, i.e. , the general population.…”
Section: Discussionmentioning
confidence: 99%